2018
DOI: 10.1111/ijal.12227
|View full text |Cite
|
Sign up to set email alerts
|

“Justice demands that you find this man not guilty”: A transitivity analysis of the closing arguments of a rape case that resulted in a wrongful conviction

Abstract: Courtroom language is renowned for being strategic and a powerful means of manipulation, which may explain why criminal cases can sometimes result in a wrongful conviction. One such case is examined here, whereby an innocent man is convicted by a jury for the rape of a minor. Through a look at the closing arguments by the prosecution and defence attorneys, we can gain insights into why the defendant finds himself wrongly convicted of sexual assault. To show how the accused and others are portrayed, a combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…This paper adopted both quantitative and qualitative methods. Bartley (2018) pointed out that the qualitative method aims at achieving deep inquiry in a way that the intended meaning and language structural forms used in texts are initiated. The other method tackles the recurrence of specific clause types in sentences (Bartley, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper adopted both quantitative and qualitative methods. Bartley (2018) pointed out that the qualitative method aims at achieving deep inquiry in a way that the intended meaning and language structural forms used in texts are initiated. The other method tackles the recurrence of specific clause types in sentences (Bartley, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Bartley (2018) pointed out that the qualitative method aims at achieving deep inquiry in a way that the intended meaning and language structural forms used in texts are initiated. The other method tackles the recurrence of specific clause types in sentences (Bartley, 2018). confirmed that the text is regarded as one shape of data adopted for the analysis of linguistic characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous media and social media outlets, including national and international newspapers, Instagram, Twitter, Netflix, to name few, have been reporting on cases in which people have had years of their lives and freedom unjustly stolen from them as a result of human error and that, ultimately, contributes to generating a rather flawed justice system. Examples of wrongful conviction cases that surfaced in 2021 alone include Dontae Sharpe, 1 who spent 26 years in prison for a murder that he did not commit, Joyce Watkins, 2 who spent 27 years in prison for the murder of her great niece and has just last month been exonerated, Henry McCollum and half-brother Leon Brown, 3 who spent 31 years in prison for a rape and murder that neither committed and Kevin Strickland, 4 who spent 42 years in prison for a triple murder that he did not commit. Whilst only four cases are cited here, the list is far more extensive with evidence from the National Registry of Exonerations 5 in the US suggesting that these are merely the tip of the iceberg.…”
Section: Introductionmentioning
confidence: 99%
“…Li & Sun, 2018). As language is often manipulated strategically for various purposes in courtroom discourse (Bartley, 2018), various linguistic phenomena such as vagueness, presupposition, and appraisal resources are studied in different approaches such as in pragmatic, cognitive, systemic-functional approach.…”
Section: Introductionmentioning
confidence: 99%
“…Li & Sun, 2018). As language is often manipulated strategically for various purposes in courtroom discourse (Bartley, 2018), various linguistic phenomena such as vagueness, presupposition, and appraisal resources are studied in different approaches such as in pragmatic, cognitive, systemic-functional approach.Transitivity analysis is a significant tool in the systemic-functional approach, which is an important perspective in analysing legal language. Transitivity analysis can help delve into how people construe the experiential meaning in courtroom situations by analysing process types, participants and contexts of the processes.…”
mentioning
confidence: 99%